Growing Plums in Florida - Ali Sarkhosh; Mercy Olmstead; E. P. Miller; Peter C. Andersen; Jeffrey G. Williamson (EDIS)
Plums could be a potential crop for growers and homeowners in Florida and other mild winter areas throughout the Gulf coast, but many plum varieties from the west coast will not consistently perform well enough in Florida to produce fruit. However, the University of Florida's stone fruit breeding program has developed cultivars that improve the potential for growing plums in Florida and other mild winter areas that have high disease pressure. These cultivars are recommended for trial in Florida. The names of all University of Florida plum cultivars begin with the prefix 'Gulf.' These cultivars are Japanese type plums (Prunus salicina Lindl.) and have resistance to plum leaf scald (Xylella fastidiosa) and bacterial spot (Xanthomonas campestris). Fruit size is satisfactory (about 1½ to 2 inches in diameter) with good fruit quality. They ripen in early to late May, approximately two weeks before plums from other areas arrive in the marketplace. This 13-page publication is a minor revision written by A. Sarkhosh, M. Olmstead, E. P. Miller, P. C. Andersen, and J. G. Williamson, and publsihed by the Horticultural Sciences Department, September 2018.